Pengaruh Kelengkapan Fasilitas, Kualitas Sumber Daya Manusia, dan Kondisi Lingkungan Kerja terhadap Kinerja Pegawai pada Kantor Kementerian Agama Provinsi Kalimantan Selatan - Addieni Nurkhairita; Purboyo Purboyo; Fanlia Adiprimadana Sanjaya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is intended to examine the extent to which the existence of infrastructure, the quality of the apparatus, and the atmosphere of the work environment have an impact on employee performance at the agency of the Office of the Ministry of Religious Affairs of South Kalimantan Province. The background of this study comes from the identification of problems that include limited supporting infrastructure, stagnation in developing human resource potential, and a work climate that is not conducive to productivity. This research applied a quantitative approach with a population coverage of all apparatus totaling 177 individuals, and involved 64 respondents who were purposively selected based on the Slovin formula. Data collection techniques were carried out through distributing questionnaires, then analyzed using multiple linear regression through SPSS software. The study findings show that partially: (1) the existence of facilities significantly affects performance; (2) human resource competence has significant implications for performance; and (3) the work environment also has a significant influence on performance. Collectively, the three variables significantly contribute to improving employee performance in the Office of the Ministry of Religious Affairs of South Kalimantan Province.